A Multivariate Analysis of Suicide Ideation Among University Students in the Philippines - Sta. Maria, Madelene A. (Animo Repository, 2015)
Suicide ideation is a robust predictor of suicide completion. Research into the extent of and the factors related to suicide ideation is thus important. Findings can help inform the development of prevention programs. Despite the increasing suicide cases among the youth in the Philippines, substantive local studies on suicide ideation are sparse. This survey determined the prevalence and associated factors of suicide ideation among university students in Manila, Philippines. A questionnaire containing items on suicide ideation and risk factors was administered among 2,450 students enrolled at a private university. As the criterion variable, suicide ideation, which was originally measured using a Likert-based statement, was recoded into a dichotomous variable for the purpose of the present analysis. Using multivariate logistic regression, the risk factors, including seven socio-demographic variables, three mental and psychological variables, two lifestyle-related variables, and four variables on social groups and relationships, were examined for their statistical associations with suicidal thoughts. The prevalence of suicide ideation among the participants was 24%, albeit the level of severity of suicidal thoughts was low. None of the socio-demographic variables was associated with suicide ideation. Multivariate analyses showed that students who were dissatisfied with one’s love relationship (OR=2.33; 95% CI=1.52-3.59); and those who reported low levels of closeness with parents (OR=1.68; 95% CI=1.15-2.46) and with peers (OR=2.56; 95% CI=1.76-3.74) were more likely to think of suicide. Based on our knowledge, this survey was the first to provide substantive evidence on suicide ideation among university students in the Philippines. The data suggest that a prevention program is necessary, at least for the private university surveyed, given that suicide ideation was prevalent among the university student respondents. There is a need for a reliable clinical follow-up of students with suicidal thoughts in order to confirm the presence of their mental health problem. The study underscores the importance of integrating the roles of primary social groups and relationships into the design of the program seeking to help the students at-risk.